Thermal and swirl flow topologies in a twisted square duct with a multi-twisted tape installed - Pitak PROMTHAISONG; Varesa CHUWATTANAKUL; Smith EIAMSA-ARD (My University, 2020)
This paper presents 3D numerical investigation of the turbulent flow and heat transfer characteristics of a twisted square duct installed with multi-twisted tapes. Air was used as the working fluid with flow rates in terms of Reynolds numbers ranging from 3000 to 20,000. The effects of (1) multi-twisted tape width ratios (w/H) of 0.2 to 1.0 and (2) the number of channels (N = 2 and 4) on heat transfer and flow mechanisms were studied at constant twist ratio of y/D = 3.5. The numerical results showed that twisted square duct combined with twisted tape caused swirl flows which effectively promoted fluid mixing and provided heat transfer over those of both a straight smooth square duct and twisted square duct. Increasing w/H led to increases in both heat transfer and the friction factor. At a given multi-twisted tape width ratio (w/H), the heat transfer and friction factor with N = 4 were higher than those with N = 2, while thermal enhancement factor showed the opposite trend. A maximum thermal enhancement factor of 1.93 was obtained at tape width ratio of w/H = 1.0, channel number of N = 2 and Re = 3000.
Keywords: Heat transfer enhancement; Square (algebra); Friction Factor; Friction loss; Heat Transfer and Optimization